2015
DOI: 10.3389/fnbeh.2015.00037
|View full text |Cite
|
Sign up to set email alerts
|

Dicholine succinate, the neuronal insulin sensitizer, normalizes behavior, REM sleep, hippocampal pGSK3 beta and mRNAs of NMDA receptor subunits in mouse models of depression

Abstract: Central insulin receptor-mediated signaling is attracting the growing attention of researchers because of rapidly accumulating evidence implicating it in the mechanisms of plasticity, stress response, and neuropsychiatric disorders including depression. Dicholine succinate (DS), a mitochondrial complex II substrate, was shown to enhance insulin-receptor mediated signaling in neurons and is regarded as a sensitizer of the neuronal insulin receptor. Compounds enhancing neuronal insulin receptor-mediated transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 127 publications
(214 reference statements)
5
21
0
Order By: Relevance
“…Various challenges, such as acute hypoxia, exposure to toxicity, chronic stress, and cerebral ischemia, were shown to stimulate IGF‐2 expression, which is considered to be neuroprotective . Our own work revealed that treatment with insulin receptor sensitizers upregulated hippocampal IGF‐2 during stress and interfered with susceptibility to a stress‐induced syndrome . Binding of IGF‐2 to IR‐A was also shown to result in preferential activation of numerous signaling pathways regulating metabolic and mitogenic responses, which were not shown for insulin, such as IGF‐2‐induced neural stem cell proliferation …”
Section: Isoforms Of Insulin Receptor In Cns and Their Localizationmentioning
confidence: 92%
“…Various challenges, such as acute hypoxia, exposure to toxicity, chronic stress, and cerebral ischemia, were shown to stimulate IGF‐2 expression, which is considered to be neuroprotective . Our own work revealed that treatment with insulin receptor sensitizers upregulated hippocampal IGF‐2 during stress and interfered with susceptibility to a stress‐induced syndrome . Binding of IGF‐2 to IR‐A was also shown to result in preferential activation of numerous signaling pathways regulating metabolic and mitogenic responses, which were not shown for insulin, such as IGF‐2‐induced neural stem cell proliferation …”
Section: Isoforms Of Insulin Receptor In Cns and Their Localizationmentioning
confidence: 92%
“…Increased activation of GSK3 was detected in postmortem brain regions from patients with major depression [31] and in brains of rodents displaying depression-like behaviors, such as learned helplessness [9], social defeat stress [10], and anhedonia [32]. Expression of constitutively active GSK3 in knockin mice increases susceptibility to depression-like behaviors [9].…”
Section: Cns Diseases Involving Psychological Stress Inflammation Anmentioning
confidence: 99%
“…This has tremendous consequences for diseases with an inflammatory component, such as multiple sclerosis, as inhibiting GSK3 even after the first episode is sufficient to reduce the relapse and the severity of EAE in mice [19,20]. Although controlling Th17 and IL-17 signaling may be one of the mechanisms whereby GSK3 promotes EAE, other actions of GSK3 may be involved in disease progression, such as promoting infiltration of inflammatory cells through the weakened BBB [14,32,47] and the production of cytokines [16], and decreasing PD-1 expression [60]. Altogether, inhibiting GSK3 may provide therapeutic benefits for multiple sclerosis and other inflammatory diseases.…”
Section: Figurementioning
confidence: 99%
“…In addition, insulin resistance displayed by obese db/db mice in brain areas with high density of insulin receptors, such as the hippocampus and cortex, is associated with emotional alterations Kim et al, 2011). Conversely, compounds enhancing neuronal insulin receptor-mediated transmission in the hippocampus show antidepressant-like effects in preclinical paradigms of depression (Cline et al, 2012;Cline et al, 2015). In line with these findings, recent pharmacological studies highlight the antidepressant properties of several antidiabetic drugs, which may involve, beyond improvement of hyperglycemia, positive impact on inflammation and neuronal activity Pomytkin et al, 2015).…”
Section: Role Of Insulin Resistancementioning
confidence: 99%